2003
DOI: 10.1016/s0896-6273(03)00086-2
|View full text |Cite
|
Sign up to set email alerts
|

The Presynaptic Active Zone Protein Bassoon Is Essential for Photoreceptor Ribbon Synapse Formation in the Retina

Abstract: The photoreceptor ribbon synapse is a highly specialized glutamatergic synapse designed for the continuous flow of synaptic vesicles to the neurotransmitter release site. The molecular mechanisms underlying ribbon synapse formation are poorly understood. We have investigated the role of the presynaptic cytomatrix protein Bassoon, a major component of the photoreceptor ribbon, in a mouse retina deficient of functional Bassoon protein. Photoreceptor ribbons lacking Bassoon are not anchored to the presynaptic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
421
3
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 413 publications
(468 citation statements)
references
References 35 publications
23
421
3
4
Order By: Relevance
“…When only synaptic transmission is compromised, the a-wave component, reflecting activity of rod and cone photoreceptors (Lamb, 1996), is spared, while the b-wave, reflecting predominantly rod or cone depolarizing bipolar cell (DBC) activity (Robson & Frishman, 1995, 1998Kofuji et al, 2000;Sharma et al, 2005), is reduced. This "negative" ERG pattern has now been reported in mice with mutations in genes encoding mGluR6 (Masu et al, 1995), nyctalopin (Pardue et al, 1998), the G-protein subunit Gα O1 (Dhingra et al, 2000(Dhingra et al, , 2002, the β 2 subunit of VDCCs (Ball et al, 2002), the presynaptic cytomatrix protein bassoon (Dick et al, 2003), or calcium-binding protein 4 (Haeseleer et al, 2004). The wide variety of proteins essential for normal synaptic transmission is suggestive of the intricacy of the synaptic complex linking photoreceptors and DBCs.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…When only synaptic transmission is compromised, the a-wave component, reflecting activity of rod and cone photoreceptors (Lamb, 1996), is spared, while the b-wave, reflecting predominantly rod or cone depolarizing bipolar cell (DBC) activity (Robson & Frishman, 1995, 1998Kofuji et al, 2000;Sharma et al, 2005), is reduced. This "negative" ERG pattern has now been reported in mice with mutations in genes encoding mGluR6 (Masu et al, 1995), nyctalopin (Pardue et al, 1998), the G-protein subunit Gα O1 (Dhingra et al, 2000(Dhingra et al, , 2002, the β 2 subunit of VDCCs (Ball et al, 2002), the presynaptic cytomatrix protein bassoon (Dick et al, 2003), or calcium-binding protein 4 (Haeseleer et al, 2004). The wide variety of proteins essential for normal synaptic transmission is suggestive of the intricacy of the synaptic complex linking photoreceptors and DBCs.…”
Section: Introductionmentioning
confidence: 75%
“…These mice involve the β 2 subunit of the VDCC (Ball et al, 2002;Gregg et al, 2002) or calcium-binding protein 4 (Haeseleer et al, 2004). Similar abnormalities also have been noted in mice lacking expression of bassoon (Dick et al, 2003) as well as in mice that lack functional rod or cone photoreceptors (Claes et al, 2004). In comparison, mice with mutations in the postsynaptic proteins mGluR6, nyctalopin or G α0 , do not share these morphological abnormalities (Pardue et al, 2001;Ball et al, 2003;Masu et al, 1995;Tagawa et al, 1999;Dhingra et al, 2000Dhingra et al, , 2002.…”
Section: Role Of the α 1f Subunit Of The Vdcc In Synaptic Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, either they do not express this protein or the epitope recognized by the antibody is uniquely modified or somehow unavailable in the bipolar cell. Bassoon appears to be crucial for maintaining photoreceptor ribbon orientation in relation to other synaptic structures, judging from the finding that in a bassoon knockout (Dick et al, 2003), both cone and rod ribbons become free-floating. Moreover, tom Dieck et al (2005) showed that bassoon is linked both to the ribbon and to the presynaptic plasma membrane/arciform density compartment, consistent with its proposed role as an anchoring protein for the ribbon.…”
Section: Ribbon Synapse-associated Proteinsmentioning
confidence: 99%
“…The effect of a bassoon knockout on bipolar cell ribbons was not reported. The presence of bassoon and the correct positioning of ribbons at active zones also are necessary for normal synaptic transmission in photoreceptors, as evidenced by altered b-waves in ERG's of bassoon mutants (Dick et al, 2003). Similarly, bassoon is necessary for the placement of synaptic ribbons at cochlear hair cell active zones and fast, synchronous neurotransmitter release (Khimich et al, 2005).…”
Section: Ribbon Synapse-associated Proteinsmentioning
confidence: 99%